Pentahelix Collaboration as a Formulation for Combating Sexual Harassment in Higher Education: A Systematic Literature Review - Wulandari, Septi; Suprapti, Suprapti; Septian, Esa; Ximenes, Manuel (Universitas Medan Area, 2025)
Globally, the number of sexual disclosures (SH) in academia reaches 58%, the second highest after the military sector. This problem remains unresolved due to a lack of internal support and cross-sector mentoring. This study aims to formulate a Pentahelix collaboration model to mitigate SH in higher education. The research method uses a systematic literature review (PRISMA). The results show that a lack of understanding of gender equality and a culture of silence cause SH in higher education. Prevention of SH begins with policies that regulate and accommodate higher education for the benefit of victims. The main obstacle is the lack of understanding of gender equality and the evaluation of SH cases. Additionally, limited mass media space is another obstacle. For the effectiveness of the policy, collaboration between the government, private sector, community, media, and academics is essential through the Pentahelix. The government is responsible for developing law enforcement, while other sectors are aware of the negative impacts of violence against children. The researcher proposes eight phases for policy implementation, starting from defining violence against children to assessing policies that have been implemented.